Narrative distance in Henry James’ The portrait of a lady - Bampoh-Addo, Richard; Mokani, Japeth (Advances in Social Sciences Research Journal, 2017)
This study sought to study narrative distance in Henry James’ The Portrait of a Lady. It analyzed the narrative to show how information is dramatically presented to minimize authorial intrusion. The study used Gerard Genette’s Narrative Discourse on the narrative as the instrument for determining how the narrative achieved narrator distance. The analysis focused on the narration of events and narration of speech to determine the range of distance between the narrator and the fictive elements in the narrative. The study revealed through the analysis that narrator distance increases when the narrator presents information from the perspective of the characters themselves, and there is a scenic, experiential approach to characterization and events that provide maximum information to the reader. Consequently, The Portrait of a Lady is an exemplar of the modernist narrative that tried to produce the novel like drama.